1996
DOI: 10.1042/bj3190307
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of human topoisomerase IIα into etoposide-resistant cells: transient increase in sensitivity followed by down-regulation of the endogenous gene

Abstract: We have investigated the possibility of overcoming the resistance of human brain tumour cells (HBT20) to etoposide by transferring the normal human topoisomerase II alpha (H-topo II) gene into these cells. H-topo II in a mammalian expression vector containing a glucocorticoid-inducible mouse mammary tumour virus (MMTV) promoter was transfected into etoposide-resistant HBT20 cells (HBT20-hTOP2MAM). HBT20 cells transfected with pMAMneo vector alone served as control cells (HBT20-MAM). These were stable transfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…RNA was extracted, electrophoresed, transferred and hybridised with a human Topo IIa gene probe (generous gift of Dr L Liu, Robert Wood Johnson Medical School, University of Medicine and Dentistry of New Jersey, NJ, USA), Topo IIa cDNA fragment, which was amplified from a single-stranded cDNA library using primer set 5 0 -GGAGAGCAGCAACAAAAACA-3 0 (3953 -3972) and 5 0 -CTTGCTTGTGACTGCTTTCG-3 0 (4484 -4503), b-actin probe (generous gift of Dr Eugenie S Kleinerman, University of Texas, MD Anderson Cancer Center), or human glyceraldehyde 3-phosphate dehydrogenase cDNA (Asano et al, 1996a). RT -PCR was performed according to the manufacturer's instructions (Takara, Ootsu).…”
Section: Northern Blot Analysis and Rt -Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA was extracted, electrophoresed, transferred and hybridised with a human Topo IIa gene probe (generous gift of Dr L Liu, Robert Wood Johnson Medical School, University of Medicine and Dentistry of New Jersey, NJ, USA), Topo IIa cDNA fragment, which was amplified from a single-stranded cDNA library using primer set 5 0 -GGAGAGCAGCAACAAAAACA-3 0 (3953 -3972) and 5 0 -CTTGCTTGTGACTGCTTTCG-3 0 (4484 -4503), b-actin probe (generous gift of Dr Eugenie S Kleinerman, University of Texas, MD Anderson Cancer Center), or human glyceraldehyde 3-phosphate dehydrogenase cDNA (Asano et al, 1996a). RT -PCR was performed according to the manufacturer's instructions (Takara, Ootsu).…”
Section: Northern Blot Analysis and Rt -Pcrmentioning
confidence: 99%
“…Proteins from whole-cell lysate were prepared for SDS -polyacrylamide gel electrophoresis by addition of an equal volume of SDS sample buffer (4% SDS, 0.2 M DTT, 20% glycerol) and boiling for 5 min. Samples were electrophoresed (1 Â 10 5 cells lane À1 ) on 7% SDS -polyacrylamide gels and transferred onto nitrocellulose membranes as described previously (Zwelling et al, 1989;Harris and Hochhauser, 1992;Asano et al, 1996a;Zhang et al, 1999). Blots were probed with human Topo I antibody (TopoGEN, Inc., Columbus, OH, USA) and monoclonal antibodies 8D2, which recognise the M r 170 000 form of the Topo IIa enzyme (kindly provided by Dr A Kikuchi, Laboratory of Medical Micology, Research Institute of Disease Mechanism and Control, Nagoya University School of Medicine, Nagoya).…”
Section: Immunoblot Analysis Of Topo IImentioning
confidence: 99%
“…5 The catalytic activity of Topo II in mammalian cells is mediated by two isoforms [ie, Topo II ␣ (TOP2A) and Topo II ␤]. 6 In vitro studies [7][8][9][10] have suggested that sensitivity to Topo II inhibitors is dependent on the expression level of TOP2A in target cancer cells. Cells with a low concentration of TOP2A protein are less sensitive to Topo II-inhibiting drugs versus cells containing a high concentration of TOP2A.…”
mentioning
confidence: 99%
“…In vitro studies have shown that the sensitivity of cancer cells to topo inhibitors is at least partly dependent on the expression of the topo II gene. 48 Drug-sensitive cells express high amounts of topo II whereas drug-resistant cells have low amounts of topo II. [49][50][51] For our study on topo IIa, we chose a collection of MCL cases from 1975 to 1985 for two reasons.…”
Section: Tablementioning
confidence: 99%